The development of game-based learning media by using educaplay to increase student motivation and participation - M. Mukni’ah; M. Mudrikah; Yolla Rizky Presbianti (Research and Development in Education (RaDEn), 2025)
This research and development aims to: 1) produce game-based learning media with Educaplay to increase student motivation and participation, 2) test the feasibility and effectiveness of game-based learning media with Educaplay. The research method applied is research and development using the ADDIE Model, which includes needs analysis, content and design planning, media development, implementation, and evaluation .The test subjects in this study were material experts Al Quran Hadith and media experts and students at State Islamic High School 1 Jember. Qualitative data analysis techniques applied in this research are data collection, data condensation, data analysis, and conclusion drawing. The quantitative data is done by: (1) Collecting scores, (2) Calculating Percentages, (3) Interpretation of Percentage Results, (4) Qualitative Analysis of Comments. Based on the results of the validation test by material experts on game-based Al-Qur'an Hadith learning media using Educaplay, a total percentage of 89% was obtained in the “Very Feasible” category. While the results of the validation test by media experts on game-based Al-Qur'an Hadith learning media using Educaplay, it was obtained a total percentage of 93% with the category “Very Feasible”. As for student responses, this game-based Al-Qur'an Hadith learning media is considered very feasible with a percentage of 85% and effective in learning usage. In addition, the experiment done in the class indicated that this media is effective in improving students' understanding of Al Quran Hadith material, as well as being able to increase student engagement and motivation in learning.